2021
DOI: 10.1111/1755-0998.13396
|View full text |Cite
|
Sign up to set email alerts
|

The Meishan pig genome reveals structural variation‐mediated gene expression and phenotypic divergence underlying Asian pig domestication

Abstract: There are wide genomic and phenotypic differences between Asian and European pig breeds, yet the current reference genome is the European Duroc pig genome. A highquality pig genome is lacking for genetic analysis of agricultural traits in Asian pigs.Here, using a hybrid approach, a high-quality reference genome (MSCAAS v1) for the Asian Meishan breed is assembled with a contig N50 size of 48.05 Mb. MSCAAS v1 outperforms the Duroc genome as a reference genome for Asian breeds. Genomic comparison reveals 49,103 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 79 publications
(108 reference statements)
2
18
0
Order By: Relevance
“…Despite the fundamental role of genome assemblies in biological studies, high‐quality assemblies are limited to well‐known domestic pig breeds. For example, all currently available chromosome‐level assemblies were from domestic breeds, including Duroc (Groenen et al, 2012; Warr et al, 2020), Bama (Zhang et al, 2019a), Luchuan (Yang et al, 2019), Ningxiang (Ma et al, 2022) and Meishan (Zhou et al, 2021), whereas the scaffold‐level assemblies also came from domestic breeds, including Wuzhishan (Fang et al, 2012), Large White, Landrace, Berkshire, Hampshire, Pietrain, Bamei, Jinhua, Rongchang and Tibetan (Li et al, 2017). For wild boars, there are some short‐read Illumina sequences (Bosse et al, 2015; Frantz et al, 2015; Groenen, 2016), but no assembly of a genome based on long‐reads or long‐range sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fundamental role of genome assemblies in biological studies, high‐quality assemblies are limited to well‐known domestic pig breeds. For example, all currently available chromosome‐level assemblies were from domestic breeds, including Duroc (Groenen et al, 2012; Warr et al, 2020), Bama (Zhang et al, 2019a), Luchuan (Yang et al, 2019), Ningxiang (Ma et al, 2022) and Meishan (Zhou et al, 2021), whereas the scaffold‐level assemblies also came from domestic breeds, including Wuzhishan (Fang et al, 2012), Large White, Landrace, Berkshire, Hampshire, Pietrain, Bamei, Jinhua, Rongchang and Tibetan (Li et al, 2017). For wild boars, there are some short‐read Illumina sequences (Bosse et al, 2015; Frantz et al, 2015; Groenen, 2016), but no assembly of a genome based on long‐reads or long‐range sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…When we combined the analysis of SV distribution and the location of gene gain and loss on the 3D4/21 cell chromosome, it was found that there was a close relationship between structural variation and gene function, which was consistent with previous reports. It has been found that the deletion of 281 bp in the first intron of MYL4 in Ningxiang pigs promoted the formation of subcutaneous fat [ 39 ], and the deletion of the intron of IGF2R in Tibetan pigs inhibited its growth rate [ 27 ]. By further combining Hi-C data, we found that the deletion of large fragments resulted in the change in 3D genomic domains in 3D4/21 cells, leading to gene dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research on the structural variation in porcine alveolar macrophages has mostly consisted of comparative analyses among breeds, but the research on the structural variation in porcine alveolar macrophages is very limited [ 24 , 25 , 26 ]. Zhou et al found a specific SV region on the X chromosome spanning 30 Mb in Asian domestic pigs by further analysis of the newly assembled Meishan pig genome [ 27 ]. Liu et al analyzed the structural variation in the litter sizes of Xiang pigs and identified 4637 and 4119 unique structural variations in the high-litter array and the low-litter array, respectively, and the related genes involved in these SVs are related to the reproductive traits of pigs [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Sus scrofa 11.1 genome of Duroc breed was selected as the reference genome. Suhuai pig contains Chinese local pig and European pig lineage, however, compared with the reference genome of Chinese local pigs (such as Meishan pig) (Zhou et al, 2021 ), Luchuan pig (Yang et al, 2019 ), and European wild boar (Groenen et al, 2012 ), the reference genome of Duroc is the standard reference genome by NCBI ( https://www.ncbi.nlm.nih.gov/data‐hub/genome/GCF_000003025.6/ ). The annotation information of the Duroc's reference genome is more complete and highly recognized, and is maintained in real time by NCBI (Warr et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%